COMPARATIVE ANALYSIS OF CUSTOMER PAYMENTS PREFERENCE BETWEEN CASH PAYMENT AND DIGITAL PAYMENT TO CUSTOMER AT INNOVATION AND ENTREPRENEURSHIP CENTER UNIVERSITY OF SAM RATULANGI - Immanuel, Julyandro; Lapian, Joyce; Pandowo, Merinda (Universitas Sam Ratulangi, 2024)
This study aims to analyze the differences in consumer preferences between cash and digital payments, considering factors such as ease of use, security, and cost. Data were collected through questionnaires from 100 respondents using a quantitative approach. Data analysis was conducted using an independent sample t-test to examine differences in the variables being tested. The results showed a significant difference in consumer payment preferences for the security factor, while no significant differences were found in consumer preferences for ease of use and cost between cash and digital payments. These findings can serve as a reference for the Innovation and Entrepreneurship Center to enhance payment facilities, ensuring consumer comfort and optimal transaction processes. Keyword: Payment Preference, Cash Payment, Digital Payment, Ease Of Use, Security, Cost